PBMC-Humanized Mouse Model for Multiple Sclerosis: Studying Immune Changes and CNS Involvement - Anastasia Dagkonaki; Irini Papazian; Vasileios Gouzouasis; Ariadni Karles; Maria Kourouvani; Theodore Tselios; Eirini Fragkiadaki; Lesley Probert (Bio-Protocol)
Humanized immune system (HIS) mice are powerful tools for studying human immune system function and dysfunction and developing human-specific immunotherapeutics. The availability of sophisticated super immunodeficient mouse strains has allowed immune system humanization using transplants of human peripheral blood mononuclear cells (PBMC) or hematopoietic stem cells. HIS mice are used extensively in immune-oncology, while there are fewer studies in autoimmunity, especially multiple sclerosis (MS). Using the protocol described here, we generated HIS mice that show key features of MS not represented in other widely used MS models [1]. Severely immunodeficient NOD.Cg-B2mem1Tac Prkdcscid Il2rgtm1Sug/JicTac (B2m-NOG) mice, which lack murine B, T, and NK cells and murine major histocompatibility class I molecules and have defective innate immune responses, were transplanted with PBMC from HLA-DRB1-genotyped MS patients and healthy donors. Mice were successfully engrafted with hCD4 and hCD8 T and B lymphocytes and developed both spontaneous and experimental autoimmune encephalomyelitis (EAE)-enhanced T-cell lesions in the central nervous system. B-cell engraftment was highest in mice receiving cells from MS patients with serological evidence for Epstein–Barr virus (EBV) reactivation. This humanized MS model shows advantages over EAE, particularly spontaneous hCD8 T-cell lesions in the brain and spinal cord, mixed hCD8/hCD4 T-cell lesions in EAE-immunized mice, and more severe lesions in mice engrafted with PBMC from MS donors carrying the DRB1*15 MS susceptibility allele compared to DRB1*15-positive healthy and DRB1*13-positive MS donors. MS HIS mice represent simple and rapid tools for investigating human immunopathology and the efficacy of therapeutics at a personalized level.